STUDI KOMPARATIF PROFITABILITAS SEBELUM DAN SESUDAH PENERAPAN BRANCHLESS BANKING DAN DAMPAK TERHADAP KEUANGAN BERKELANJUTAN - Pranata S., Andika Nedya; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The purpose of this study was to determine a comparative study of banking profitability before and after implementing branchless banking, as well as analyzing the impact of the branchless banking program on sustainable finance. This research takes bank companies that are included in the Bank Based on Core Capital (KBMI) 4 group, namely Bank Mandiri, BRI, BNI, and BCA as research objects. Apart from that, one of the impacts of branchless banking on the macro economy is economic growth. The time period reviewed in this research is from 2010-2014 before the use of branchless banking and 2015-2022 after the use of Branchless Banking. This research uses a comparative test method and the hypothesis test uses non-parametric statistics (Wilcoxon signed-rank test). The research results show that in the ROA ratio there are 3 banks that show significant differences, in the NIM ratio there are 3 banks that show significant differences, and in the BOPO ratio 2 banks show significant differences. The results of this research also show that the existence of branchless banking has a positive impact on the macro economy, namely economic growth in